Adanya Keterkaitan Antara Perhatian Orangtua Dengan Kemandirian Belajar Anak - Andriyani, Silvia; Utami, Adnani Budi; Ramadhani, Hetti Sari (JIWA: Jurnal Psikologi Indonesia, 2023)
This study aims to determine whether there is a relationship between parental attention and children's learning independence at Ana Maritim Elementary School. The population of this research was 62 students of class IV, V, and VI. Using the subject of students in grades IV, V, and VI to find out whether grades IV, V, and VI have independent learning. Data analysis techniques in this study used IBM Statistics version 25 for windows. The results of the Spearman Rho non-parametric correlation test obtained a correlation coefficient of 0.399 with a significance level of 0.001 (<0.01). From the results of the correlation test in this study, it can be concluded that there is a positive correlation with the level of a strong relationship between the variables of parental attention and children's learning independence. This has the meaning that the higher the parental attention, the higher the child's learning independence and vice versa if the lower the parental attention, the lower the child's learning independence. Penelitian ini bertujuan untuk mengetahui ada tidaknya hubungan antara perhatian orang tua dengan kemandirian belajar anak Di SD Ana Maritim. Populasi penelitian ini adalah Siswa/i kelas IV, V, dan VI sebanyak 62 orang. Memakai subjek siswa kelas IV, V, dan VI untuk mengetahui apakah pada rentang kelas IV, V, dan VI telah memiliki kemandirian belajar. Teknik analisis data dalam penelitian ini menggunakan IBM Statistic versi 25 for windows. Hasil uji korelasi teknik non- parametric Spearman Rho dengan diperoleh koefisien korelasi 0,399 dengan taraf signifikansi 0,001 (<0,01). Pada hasil uji korelasi penelitian ini dapat ditarik kesimpulan bahwasannya terdapat korelasi yang positif dengan tingkat hubungan yang kuat antara variabel perhatian orangtua dengan kemandirian belajar anak. Hal tersebut memiliki makna bahwasannya semakin tinggi perhatian orangtua maka akan semakin tinggi kemandirian belajar anak begitu juga dengan sebaliknya jika semakin rendah perhatian orangtua maka akan semakin rendah kemandirian belajar anak.